Distinguishing the histological and radiological features of cystic lung disease in Birt–Hogg–Dubé syndrome from those of tobacco‐related spontaneous pneumothorax. Issue 5 (26th December 2013) - Fabre, Aurelie; Borie, Raphael; Debray, Marie Pierre; Crestani, Bruno; Danel, Claire
<x xml:space="preserve">Abstract</x> Aims Birt–Hogg–Dubé syndrome (BHD) is a rare autosomal dominantly inherited genodermatosis that predisposes to cystic lung disease, leading to spontaneous pneumothoraces. This retrospective analysis of five BHD cases (two men, three women) compared lung histology and computed tomography (CT) imaging to a matched cohort of non‐BHD patients with spontaneous pneumothoraces (SPN). Methods and results Lung was sampled during pleurodesis to resect bullae. Recurrent pneumothoraces was seen in two patients. Fourteen sets of histological slides (seven in each group) and 10 CT scans (five in each group) were reviewed. CT scans in BHD showed multiple cysts with a basal predominance and intraparenchymal/peribronchial distribution. On histological examination, BHD lungs showed punch‐out cysts with no inflammation, and lacked subpleural fibroelastotic scars and smoking changes. In contrast, all SPN cases showed respiratory bronchiolitis and subpleural fibroelastotic scars. Conclusions This study emphasizes the importance of smoking history and topography of the lesions in assessing cystic lung disease. Pathologists need to remain alert to the possibility of BHD in the setting of recurrent pneumothoraces in a non‐smoker, in particular in a woman, at any age, and should take part in a multidisciplinary approach to the diagnosis of cystic lung disease to obtain clinical and CT scan details.